2021
DOI: 10.3390/cancers13071490
|View full text |Cite
|
Sign up to set email alerts
|

3D Model Characterization by 2D and 3D Imaging in t(14;18)-Positive B-NHL: Perspectives for In Vitro Drug Screens in Follicular Lymphoma

Abstract: Follicular lymphoma (FL) is an indolent B cell lymphoproliferative disorder of transformed follicular center B cells, which accounts for 20–30 percent of all non-Hodgkin lymphoma (NHL) cases. Great advances have been made to identify the most relevant targets for precision therapy. However, no relevant models for in vitro studies have been developed or characterized in depth. To this purpose, we generated a 3D cell model from t(14;18)-positive B-NHL cell lines cultured in ultra-low attachment 96-well plates. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 58 publications
0
12
0
1
Order By: Relevance
“…In the current study, we observed that B-NHL cells are grown within an ultra-low attachment plate or a hanging drop method aggregating into loose clumps of cells instead of 3D structures, which was previously described. 59 Such methods may be helpful in drug studies; however, they do not support cell–cell and microenvironment interactions. Here, we observed that the lymphoma cells form tight spheroids with agarose gel; however, the cells disintegrate when transferred with a pipette for further examination.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we observed that B-NHL cells are grown within an ultra-low attachment plate or a hanging drop method aggregating into loose clumps of cells instead of 3D structures, which was previously described. 59 Such methods may be helpful in drug studies; however, they do not support cell–cell and microenvironment interactions. Here, we observed that the lymphoma cells form tight spheroids with agarose gel; however, the cells disintegrate when transferred with a pipette for further examination.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphomas develop as complex cell structures including tumor cells and their microenvironment within mechanically constrained LN. Previous lymphoma spheroid models incorporating only malignant B cells 17,18,32 suggest that the 3D cell architecture is a key feature for the regulation of lymphoma growth and therapeutic response. LN are highly dynamic structures expanding and becoming mechanically stiff under immune cell recruitment and proliferation, whereas immune response resolution is associated with LN contraction and return to a baseline of mechanical softness 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Multicellular spheroids or tumor organoids represent promising models allowing high-throughput screening of anti-cancer drugs in versatile systems mixing several cell types and ECM components. While 3D culture models are increasingly developed for solid cancer 15 , their transfer to lymphoma modeling is still limited and includes: i) multicellular aggregates of lymphoma cells, which are obtained using the hanging drop and ultra-low attachment method, and are useful for testing drug efficacy but do not account for the effect of cell-cell and cell-ECM interactions [16][17][18] , ii) 3D lymphoma organoid models integrating lymphoid-like stromal cells or integrin-specific binding peptides recapitulating more accurately lymphoma microenvironment, but difficult to handle and low-throughput 19 , iii) a DLBCL-on-chip model utilizing lymphoma and TME murine cells, enabling the in vitro modeling of DLBCL niche and associated vasculature 20 . However, modeling the interactions of the TME with primary lymphoma B cells in 3D cocultures remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Les mono-cultures 3D de cellules encapsulées (primaires de patients ou de lignées), permettent de créer des modèles très variés reproduisant des tissus 3D simples : avec la TCC, de nombreuses cellules de tumeurs solides ont été déjà été encapsulées avec succès (Fig 1B existent sont des agrégats multicellulaires difficiles à manipuler et à imager [24][25][26]. L'encapsulation permet de les faire pousser dans un environnement clos, équivalent à un mini-bioréacteur, qui facilite leur manipulation mais également permet de les imager en petits groupes, ce qui n'est généralement pas évident pour ce type de cellules.…”
Section: -1 Mono-cultures 3d De Cellules Tumoralesunclassified